IMPROVING STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT BY USING ANTICIPATION GUIDES FOR STUDENTS OF COMMUNICATION STUDY PROGRAM OF UNIDKNAS UNIVERSITY YEAR 2017/2018 - Basmantra, Ida Nyoman (Jurnal Ilmiah Dinamika Sosial, 2018)
This study entitled Improving Students’ Reading Comprehension in Narrative Text by using Anticipation Guides for Students of Communication Study Program of Unidknas University year 2017/2018. This study uses to analyze the four major skills to be mastered by the learners, namely listening, speaking, reading, and writing. The standard competency is the general competency that should be mastered by the school graduates. The basic competency is the minimum competency that should be mastered by the students in learning a certain subject. One standard competency consists of several basic competencies. To know whether the students have achieved the basic competency, the teacher needs to refer to some indicator. One basic competency can be developed into some indicators. The subject of this study is the 40 students of Communication Study Program in Undiknas University in academic year 2017/2018. The research design of this study was action research based on Kemmis and Mc Taggart (1988) design. Richards and Plat & Plat (1999) as cited by Adnyani (2001) defined action research as a teacher initiated classroom research that seeks to increase the teacher’s understanding of classroom teaching and learning and to bring about improvements in classroom practices. The result of this study shows that there were two types of data obtained during the research namely, quantitative and qualitative data. The quantitative data was shown from the score obtained by the students in the pretest; post test I and post test II. Those data were shown in the form of tables and diagram and they were interpreted descriptively. The qualitative data were obtained from both the analysis of the diary in every session of the two cycles and also from the questionnaire which was applied to the students.Keywords: Reading Comprehension, Narrative text, Communication Study Program